Pacote de gelo e imersão em água gelada afetam o desempenho muscular e a atividade eletromiográfica - Vieira, Amilton (Universidade Federal de São Carlos, 2012)
Although tissue cooling is widely used in the treatment of musculoskeletal disorders there is still controversy about its effects on muscular performance. It is important to study this issue since cooling is also combined with exercise. Objective. To compare the effects of ice pack and cold water immersion on the muscular performance parameters of plantar flexors and electromyography (EMG) activity of the triceps surae. Design. Subjects were randomly assigned treatment with either ice pack (n=20) or cold water immersion (n=21). Independent variables were cold modality (ice pack or cold water immersion), muscle action (isometric and concentric isokinetic, angular velocity of isokinetic test (60 and 120°/s) and measurement time (pre- and post-cooling). Dependent variables were skin temperature, muscular performance and EMG activity. Methods. The sample included 41 healthy men with a mean age of 22.15 (SD=2.89). In each group one of the two cold modalities was applied to the calf region for 20 minutes. Skin temperature, plantar flexors muscular performance parameters and EMG activity of the triceps surae were measured before and after cooling. Results. Ice pack increased isometric peak torque. Both cold modalities reduced EMG activity in both muscles during isometric contraction. Both cold modalities reduced peak torque and total work during isokinetic contraction at both velocities. Ice pack was more effective at reducing EMG activity in isokinetic contractions. Limitations. The examiner was not blinded regarding treatment group and the population included only young healthy participants. Conclusions. Ice pack and cold water immersion showed similar effects on muscular performance, which depends on the muscle action performed. Cooling decreased isokinetic performance and the ice pack increased isometric torque. The results suggest that caution is required when performing activities after cooling, especially tasks involving maximal isokinetic contractions.
Keywords: Fisiologia; Crioterapia; Dinamômetro isocinético; Eletromiografia; Tornozelos; Músculo tríceps sural; Isokinetic dynamometer; Electromyography; Cryotherapy; Ankle; Triceps surae muscle; CIENCIAS BIOLOGICAS::FISIOLOGIA